2007
DOI: 10.1063/1.2472775
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of UV absorption coefficient in laser-modified fused silica

Abstract: Laser-induced damage in transparent dielectrics leads to the formation of laser-modified material as a result of exposure to extreme localized temperatures and pressures. In this work, an infrared thermal imaging system in combination with a fluorescence microscope is used to map the dynamics of the local surface temperature and fluorescence intensity under cw, UV excitation of laser-modified fused silica within a damage site. The energy deposited via linear absorption mechanisms and the absorption coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 17 publications
(14 reference statements)
0
11
0
Order By: Relevance
“…22,23 Unlike those located in surfaces, wherein silicon remains regularly coordinated, a 2-membered ring in the irradiated bulk usually contains a Si 5 defect. This unique observation indicates that the formation of such 2-membered rings is caused by laser-induced Si 5 (not the native ones), which divided the network rings into smaller ones, resulting in small Si-O-Si bond angles and thus decreased Si-Si pair distances. However, some experiments suggested that the Si-O-Si bond angles will increase after 355-nm irradiation.…”
Section: -3mentioning
confidence: 91%
See 2 more Smart Citations
“…22,23 Unlike those located in surfaces, wherein silicon remains regularly coordinated, a 2-membered ring in the irradiated bulk usually contains a Si 5 defect. This unique observation indicates that the formation of such 2-membered rings is caused by laser-induced Si 5 (not the native ones), which divided the network rings into smaller ones, resulting in small Si-O-Si bond angles and thus decreased Si-Si pair distances. However, some experiments suggested that the Si-O-Si bond angles will increase after 355-nm irradiation.…”
Section: -3mentioning
confidence: 91%
“…18 bonded to 3 Si atoms) appear and exhibit a comparable growth rate to Si 5 for the first 400 excitations. In previous studies, Si 5 are believed to be native defects in fused silica, and TBO are hypothesized as intermediate products of silicon oxidation during the formation of the amorphous network. 19 For the case of UV-laser radiation, Si 5 and TBO correspond preliminarily to an oxygen-excess and oxygen-deficiency environment, respectively, which may generate Frenkel-type defects as reported elsewhere.…”
Section: -3mentioning
confidence: 99%
See 1 more Smart Citation
“…Damage initiation sites are typically on the order of 10 µm in diameter, depending on the laser pulse length, but tend to grow exponentially under subsequent ns laser irradiation [1][2][3][4][5][6]. Microscopic examination of these sites reveals the formation of a damage crater containing modified material believed to be the result of exposure to high pressures and/or temperatures, as well as cleaved surfaces and cracks [6][7][8][9][10]. Although various models regarding the processes involved during a surface damage event have been proposed based on post-mortem examination of the crater characteristics for various laser parameters, there are only limited experimental studies that capture the dynamic processes during a damage event [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, laser systems designed to achieve laser-driven inertial confinement fusion operate near the LIB threshold of their component optics. LIB, which has shown to lead to modification of the electronic and structural properties of the host material [1][2][3][4][5][6][7], can eventually lead to the formation of a damage site. Post-mortem characterization of laser-induced damage is widely used and employs various imaging tools, for example scanning and transmission electron microscopies [5], white light scattering and photoluminescence microscopies [1,2], and optical coherence tomography [1] to name a few.…”
Section: Introductionmentioning
confidence: 99%